Using social media platforms to study the ecology and exploitation of mud lobsters in the Philippines - Albarico, Frank Paolo Jay B.; Albarico, Pinky Jee B.; Peña, Candelaria C.; Salva, Peithe Ma; Dong, Cheng-Di (Vol. 150, No. 6B (December 2021) pages 1837-1847.)
"Mud lobsters are burrowing crustaceans that are widely distributed in the Indo-Pacific region, including the Philippines. However, they are somehow neglected in scientific studies in the country." -Title page.